IMPLEMENTASI IJIN PRAKTEK DOKTER ATAU DOKTER GIGI DI KABUPATEN PONOROGO JAWA TIMUR MENURUT PASAL 37 DAN PASAL 38 AYAT (2) UNDANG-UNDANG NOMOR 29 TAHUN 2004 TENTANG PRAKTEK KEDOKTERAN - DWIYANTI, YULI (Dinamika Hukum, 2019)
Licensing of doctor's practice based on SIP Ponorogo District Health Office part of the validity period has expired, but still doing medical practice, things are not in accordance with Article 38 paragraph (2) of the Medical Practice Act No. 29 of 2004. Article 37 explains that every doctor and dentist who will practice medicine in Indonesia must have a practice permit. According to Article 1, the practice permit is written evidence provided by the government to doctors and dentists who will carry out medical practice after fulfilling the requirements. Efforts to make the practice and dentist in Ponorogo Regency can be in accordance with Articles 37 and 38 paragraph (2) of the Medical Practice Act No. 29 of 2004, especially in the practice of doctors based on SIP who still violate the regulations, namely the validity period of SIP, but still implementing the practice of medicine, which is not in accordance with Article 37 and Article 38 paragraph (2), can be seen from several elements, namely: in terms of the legal substance and legal culture, it is necessary to improve Law No. 29 of 2004 concerning Medical Practice. Due to restrictions on the place of practice, it cannot be simply set for all regions which are not in the same geographic and demographic conditions, so that they can get the services of doctors and specialist doctors equally. Requirements that are very complicated and difficult to issue STR (Registration Certificate), so it needs to be reviewed. Keywords: Implementation, Permit for Doctor Practice or Dentist